Experiencing pacific environments: pasts, presents, futures - Emde, Sina; Dürr, Eveline; Schorch, Philipp (The contemporary Pacific, 2020)
In the context of pressing environmental challenges in the Pacific and indeed the world, this special issue sheds light on the diverse ways in which people in Oceania experience environments, as well as the diverse ways in which environmental knowledge can be articulated. Inspired by previous work that conceptualizes the environment not as a given, definite, and specified entity but as a constantly changing category in relation to other agents, the articles collected here stress coactivity and entanglement and promote a broad sense of the environment in Oceania as encompassing land, water, climate, and material things in different social, political, and economic formations and spaces. By focusing on experiencing environments, this collection illuminates empirical realities and highlights people's agency and perspectives as well as their innovative capacities to retain, transform, and (re)create ways of life in their interactions with human and other-than-human entities. It advocates for equal recognition of different worlds and seeks to advance the decolonization and pluralization of scholarship. This special issue works toward this by traversing disciplinary boundaries between the arts and academia and between Indigenous and non-Indigenous epistemologies and ways of presenting and disseminating knowledge. (Contemp Pac/GIGA)